A one-step facile route synthesis of copper oxide/reduced graphene oxide nanocomposite for supercapacitor applications. Issue 1 (1st January 2018) - Sagadevan, Suresh; Zaman Chowdhury, Zaira; Johan, Mohd. Rafie Bin; Aziz, Fauziah Abdul; Salleh, Emee Marina; Hawa, Anil; Rafique, Rahman F.
Abstract: In this research, a one step, facile route has been undertaken to synthesise copper oxide/reduced graphene oxide (CuO/rGO) nanocomposites. X-ray powder diffraction analysis (XRD) was carried out to identity the crystalline structure and phase of the synthesised sample. Elemental analysis and surface morphological features were analysed using EDX and FESEM Images. Particle size as well as the shape of the as prepared composite was observed from HR-TEM images. Raman spectra illustrated the peak of the individual composite materials. The electrochemical properties of the prepared nanocomposite were investigated. The dielectric behaviour of the sample including dielectric constant, dielectric loss and AC conductivity was measured at various frequency levels. Temperature was varied accordingly to observe the effect of temperature on the dielectric properties of the sample.